Improvement in left ventricle geometry and function after kidney transplantation - Baiq Gerisa Rahmi Faharani; Hasanah Mumpuni; Yulia Wardhani; Metalia Puspitasari; Raden Heru Prasanto; Iri Kuswadi; Anggoro Budi Hartopo (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Chronic kidney disease (CKD) is associated with remodeling of the left ventricle (LV), affecting both its geometry and function. Kidney transplantation in patients with stage 5 CKD may lead to improvements in LV remodeling and result in better cardiac function. The aim of the study was to determine changes and improvements in LV geometry and function after kidney transplantation in patients with stage 5 CKD. This was an observational study conducted by collecting secondary data from the Hospital's Kidney Transplantation Registry, Dr. Sardjito General Hospital spanning the years 2017 to 2020. The study employed a comparative design, contrasting the results before and after treatment (kidney transplantation). We compared transthoracic echocardiographic parameters for LV geometry and function before and after kidney transplantation. The evaluation timeframe after kidney transplantation was divided into <12 and ³12 mo. A total of 27 patients qualified for inclusion in this study. In the <12 mon (n=20) evaluation group, there was a reduction in proportion of LV hypertrophy from 70% to 45%. There was an increase in global LV systolic function (ejection fraction) from 60.1±10.95% to 67.85±6.48% (p=0.014), and a decrease in LV diastolic dysfunction from 45% to 15% (p=0.07). In the ³12 mon (n=11) evaluation group, there was a decrease in the proportion of LV hypertrophy from 81.8 to 54.5%, an increase in global LV systolic function (ejection fraction) from 57.73±13.07% to 69.36±6.12% (p=0.011), and a decreased LV diastolic dysfunction from 63.6% to 0% (p=0.016). In conclusion, significant changes in LV geometry and function are observed following kidney transplantation, indicating improvements in these parameters. There are improvements in LV systolic function started at <12 mo and in LV diastolic function at ³12 mo after kidney transplantation.